Linear Coassembly of Upconversion and Perovskite Nanoparticles: Sensitized Upconversion Emission of Perovskites by Lanthanide‐Doped Nanoparticles. (9th September 2020) - Estebanez, Nestor; Cortés‐Villena, Alejandro; Ferrera‐González, Juan; González‐Béjar, María; Galian, Raquel E.; González‐Carrero, Soranyel; Pérez‐Prieto, Julia
Abstract: Sensitized emission of lead halide perovskite nanoparticles (LHPNPs) can be achieved by near‐infrared (NIR) excitation of nearby lanthanide‐doped upconversion nanoparticles (UCNPs) by using a low‐cost diode laser. Here, the first preparation of linear assemblies of core and core–shell NPs, as well as linear coassemblies of LHPNPs and UCNPs, within an open peapod‐like lead sulfate shell are reported. UCNPs with a NaYF4 matrix doped with ytterbium and thulium or erbium, and with an inert shell of NaYF4 in the case of core‐shell, and all‐inorganic CsPbX3 NPs (X = halide) are chosen for these studies. Interestingly, the lead sulfate shell enhances the luminescence of the core/core– shell UCNPs in the polymers by ≈20‐fold and it also plays a role in the efficiency of the sensitized emission of the LHPNPs under NIR excitation of the UCNP‐LHPNP copolymers, as well as in the chemical stability of the LHPNPs in contact with water. The (co)polymers are prepared as colloids and deposited as solid films on a glass substrate. The lifetime of the sensitized LHP emission and the efficiency of the process wholly depends on the irradiance and on the sample state. These copolymers are promising candidates for the manufacture of photonic devices. Abstract : Linear assemblies of core/core–shell upconversion nanoparticles (UCNPs), as well as coassemblies of CsPbX3 (X = halide) perovskite and UCNP, within an open peapod‐like PbSO4 shell are prepared for the first time. The UCNP polymers exhibit an enormous emission enhancement with no impact on their emission lifetime, while UCNP‐CsPbX3 copolymers display efficient harvesting of near‐infrared photons by the perovskite.